Social Support, Depression, and Anxiety as Predictors of Suicidal Ideation in People Living with HIV/AIDS: A Meta-Analysis - Aulia Putri Nugraheni; Maoli Zartika; Anis Lupita Ningrum; Bhisma Murti; Ika Yuli Ayuningrum (Journal of Health Promotion and Behavior, 2025)
Background: Acquired Immune Deficiency Syndrome (AIDS) is a disease caused by the Human Immunodeficiency Virus (HIV). People living with HIV/AIDS (PLWHA) are 7 to 36 times more likely to experience suicidal ideation compared to the general population. Suicidal ideation among PLWHA is closely correlated with depression and anxiety. Social support plays a crucial role in helping individuals cope with HIV, serving as a direct protective factor for psychosocial health. This meta-analysis aims to examine the relationship between social support, depression, and anxiety with suicidal ideation among people living with HIV/AIDS (PLWHA) Subjects and Method: The meta-analysis was conducted using the PICO framework. Population: people living with HIV/AIDS (PLWHA). Intervention: high social support, presence of depression, and anxiety. Comparison: low social support, absence of depression, and absence of anxiety. Outcome: suicidal ideation. Research data were obtained from the Google Scholar, PubMed, and ScienceDirect databases. The keywords used were “social support” OR “depression” OR “anxiety” AND “suicidal ideation” AND “HIV/AIDS” OR “PLWHA.” The inclusion criteria included cross-sectional studies published between 2014 and 2024. Data analysis was performed using RevMan version 5.4. Results: The meta-analysis included 19 primary studies conducted in Indonesia, South Korea, China, Ethiopia, Uganda, Nigeria, South Africa, and the United States, with a total sample size of 11,166 participants. PLWHA residing in communities with high social support had 0.65 times lower odds of suicidal ideation compared to those with low social support (aOR= 0.65; 95% CI= 0.57 to 0.74; p<0.001). PLWHA experiencing depression had a 3.21 times higher risk of suicidal ideation compared to those without depression (aOR= 3.21; 95% CI= 2.07 to 4.99; p <0.001). PLWHA with anxiety were 1.67 times more likely to experience suicidal ideation than those without anxiety (aOR= 1.67; 95% CI= 1.29 to 2.18; p= 0.001). Conclusion: Depression and anxiety increase the risk of suicidal ideation, whereas high social support reduces the risk of suicidal ideation among people living with HIV/AIDS.